A multimodal mixed-methods approach for holistic insights in Roux-en-Y gastric bypass patients: Protocol for a patient-centered framework - Blanca Elena Guerrero Daboin; Lucas Rosas Campelo; Beatriz Bobbio de Brito; Maria Clara da Cruz Pires; Tassiane Cristina Morais; Gustavo Peixoto Soares Miguel; Jandesson Mendes Coqueiro; Luciane Bresciani Salaroli; Andressa Bolsoni Lopes; Fabiano Kenji Haraguchi (MethodsX, 2025)
This protocol outlines the methodological approach for a multimodal mixed-methods study to investigate how social determinants impact the pre-and post-operative biochemical parameters and experiences of patients undergoing RYGB. It integrates quantitative and qualitative data from patients in a public hospital. Biochemical, anthropometric, and body composition data will be collected from 717 clinical records of patients who underwent RYGB from 2020 to 2024, with data extracted 30 days before and six months after surgery. Semi-structured interviews will be conducted with patients to explore their experiences and perspectives before and after surgery. To complement patient perceptions, a focus group will be conducted with nutritionists experienced in managing post-bariatric surgery patients to gather insights into nutritional challenges and post-surgical care strategies. The findings of this study will provide a comprehensive analysis of the short-term biochemical, anthropometric, and body composition changes in patients following RYGB surgery while shedding light on the social determinants that influence these outcomes. • This is one of the first multimodal mixed-methods studies in Brazil exploring both biochemical outcomes and lived experiences of RYGB patients in the public health system. • This study targets a vulnerable population by addressing non-communicable disease prevention through improved bariatric care.